Hubungan Masa Kerja Dengan Kadar Timbal Pengemudi Ojek Online Perokok Pangkalan Banyuraden - Aisyah Azhara; Adlina Karimina Nurul Husna; Isnin Aulia Ulfah Mu’awanah (Journal of Innovation Research and Knowledge, 2026)
Lead (Pb) exposure from air pollution and cigarette smoke can increase the risk of health problems in online motorcycle taxi drivers. This study aimed to determine the relationship between working period and blood lead (Pb) levels in smoking online motorcycle taxi drivers at Banyuraden Base. This study used a cross-sectional design with 20 respondents, and blood Pb levels were examined using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that most respondents (75%) had abnormal blood Pb levels. Data were analyzed using the Spearman correlation test. The results showed that all respondents (100%) had a working period of ≥ 1 year. Blood lead (Pb) levels had a minimum value of 0 and a maximum value of 686 µg/dL, with an average of 87.8. Most respondents (75%) had abnormal blood Pb levels. The Spearman correlation test showed a p-value of 0.034 (p < 0.05), indicating a significant relationship between working period and blood lead (Pb) levels. The longer the working period of online motorcycle taxi drivers, the higher the blood lead (Pb) levels tended to be.